2015
DOI: 10.1515/ijsl-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of immigrants’ second-language proficiency: a Dutch study of immigrants with a low level of societal participation and second-language proficiency

Abstract: This article examines the predictors of second-language proficiency for a group that until now has hardly been investigated: immigrants who rarely participate in the host society and who have a low level of second-language proficiency (sample characteristics are for example: no paid job, low educational and literacy level, high mean age and number of years since migration). In contrast with earlier research, not only self-assessments were used as indicator for second-language proficiency, but also language tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The findings showed that local language proficiency levels were about similar for men and women, but higher among refugees who were younger, who had a longer length of stay in the Netherlands, who had a higher premigration education level, and who experienced lower levels of psychological distress. The latter finding is especially important, as some earlier studies did not find a negative link between psychological distress and local language acquisition among immigrants (Van Niejenhuis et al., ; Van Tubergen, ). This could possibly be explained by our use of more reliable and valid instruments of psychological distress and language proficiency.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…The findings showed that local language proficiency levels were about similar for men and women, but higher among refugees who were younger, who had a longer length of stay in the Netherlands, who had a higher premigration education level, and who experienced lower levels of psychological distress. The latter finding is especially important, as some earlier studies did not find a negative link between psychological distress and local language acquisition among immigrants (Van Niejenhuis et al., ; Van Tubergen, ). This could possibly be explained by our use of more reliable and valid instruments of psychological distress and language proficiency.…”
Section: Discussionmentioning
confidence: 83%
“…Despite some exceptions (Van Niejenhuis et al., ; Van Tubergen, ), most previous research findings revealed a negative effect of psychological distress on local language proficiency (Beiser & Hou, ; Chiswick & Miller, ; Van Tubergen & Kalmijn, ). Psychological distress was measured with the 10‐item Kessler Psychological Distress Scale (K10; Kessler et al., ).…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations